Between Exclusion and Assimilation: Experimentalizing Multiculturalism - Bhabha, Faisal (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractWith increasing frequency, members of cultural minorities are demanding not only equality and non-discrimination as individuals, but also the legal recognition of their collective identities. Their claims to cultural protection and accommodation are necessarily philosophical, political, moral, and (both constitutionally and normatively) legal. This paper is a reflection on the last dimension, the legal axis. The author sets out to delineate the descriptive, interpretive, and normative scope of section 27 of the Canadian Charter of Rights and Freedoms. He is influenced by the approaches to constitutional innovation expounded by theories of democratic experimentalism.The first part of the paper outlines the textual and normative framework of the Charter’s multiculturalism provision. Section 27 creates two distinct types of interests that give rise to claims: one individual and one group-based, described respectively as “accommodation” and “autonomy”.The second part of the paper applies the normative framework to two case studies: female genital cutting and sharia tribunals. These examples provide a setting in which to explore the potential of section 27 to address the cultural demands in ways that go beyond conventional doctrinal and normative understandings. The author suggests that an experimentalist interpretation of multiculturalism under section 27 would create a space in which different approaches and institutional arrangements could be tried in order to determine the best practices for handling difficult, highly contextual questions. Instead of limiting possibilities by adopting restrictive approaches that extinguish cultural claims and risk radicalizing groups, the author argues that the normative force of section 27 includes an imperative to create the institutional conditions within which measures can be tried and tested, with the expectation that benchmarks will emerge through practice.